eRASSUJ060839.5-704014: A double degenerate ultra-compact binary in the direction of the LMC - Maitra, C.; Haberl, F.; Vasilopoulos, G.; Rau, A.; Schwope, A.; Friedrich, S.; Buckley, D. A. H.; Valdes, F.; Lang, D.; Macfarlane, S. A. (2024)
Context. During four all-sky surveys (eRASS1--4), eROSITA, the soft X-ray instrument aboard Spektrum-Roentgen-Gamma (SRG) detected a new supersoft X-ray source, eRASSU J060839.5-704014, in the direction of the Large Magellanic Cloud (LMC). Methods. We arranged follow-up observations in the X-ray and optical wavelengths and further searched in archival observations to reveal the nature of the object. Results. We discover pulsations at ~374 s with a pulse profile consistent with 100% modulation. We identify two other periodicities in the eROSITA data, which we establish as aliases due to the sampling of the eROSITA light curve. We identify a multi-wavelength counterpart to the X-ray source in UVW1 and g, r, i, and z images obtained by the optical/UV monitor on XMM-Newton and the Dark Energy Camera at the Cerro Tololo Inter-American Observatory. The timing and spectral characteristics of the source are consistent with a double degenerate ultra-compact binary system in the foreground of the LMC. eRASSU J060839.5-704014 belongs to a rare class of AM CVns, which are important to study in the context of progenitors of SN Ia and for persistent gravitational wave detection. Conclusions. We identify eRASSU J060839.5-704014 as a new double degenerate ultra-compact binary located in the foreground of the LMC.
Keywords: Astrophysics - High Energy Astrophysical Phenomena